Teaching Modern Macroeconomics in the Traditional Language: The IS-MR-AD-AS Model - Mendoza Bellido, Waldo (2017)
During the last two decades we have witnessed the emergence in the field of intermediate macroeconomics of an extensive literature that seeks to dismiss the traditional IS-LM-AD-AS model and replace it with the New Keynesian option. However, the efforts have not been successful, and currently most macroeconomics textbooks still rely on the traditional model, which is more than 80 years old. In order to help break this inertia, this paper proposes the IS-MR-AD-AS model, a New Keynesian model that allows determining the equilibrium values of production, inflation and the real interest rate. The model differs from the existing ones in two respects. Firstly, in the description of the model, in the graphic and mathematical treatment, and in the use of comparative static as a method to simulate the effects of the exogenous variables on the endogenous ones, the simplicity and elegance of the traditional IS-LM-AD-AS is replicated. Second, in spite of its simplicity, more complex issues can be dealt with, since the general model gives rise to four subsystems with which short-term equilibrium, steady-state equilibrium, transit toward steady-state equilibrium and rational expectations are addressed one at a time. Durante las últimas dos décadas hemos presenciado en el campo de la macroeconomía intermedia la aparición de una amplia literatura que busca desplazar al tradicional modelo IS-LM-AD-AS y reemplazarlo con la opción neokynesiana. Sin embargo, los esfuerzos no han sido exitosos, y actualmente la mayor parte de los textos de macroeconomía aun contienen el modelo tradicional, que ya tiene 80 años de vida. En un intento de romper esa inercia, este artículo propone el modelo IS-MR-AD-AS, un modelo neokeynesiano que permite determinar los valores de equilibrio de la producción, la inflación y la tasa real de interés. El modelo difiere de los existentes en dos aspectos. Primero, en la descripción del modelo, en el tratamiento gráfico y matemático, y en el uso de la estática comparativa como un método para para simular los efectos de las variables exógenas sobre las endógenas, se replica la simplicidad y elegancia del tradicional IS-LM-AD-AS. Segundo, a pesar de su sencillez, con el modelo pueden abordarse temas complejos, dado que el modelo general da lugar a cuatro subsistemas: el del corto plazo, el del equilibrio estacionario, el del tránsito al equilibrio estacionario y el de las expectativas racionales